Combined effects of climate change and éthinylestradiol on the life cycle and physiology of three-spined stickleback - Iaria, U.; Turiès, Cyril; Beaudouin, Rémy; Porcher, Jean Marc; Devergne, J.; Servili, A.; Loizeau, V.; Bado-Nilles, Anne (HAL CCSD, 2022)
International audience